2022
DOI: 10.1007/s13668-022-00402-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Aging in Early Life: Role of Maternal and Early Childhood Nutrition

Abstract: Purpose of Review Early life presents a pivotal period during which nutritional exposures are more likely to cause epigenetic modifications, which may impact an individual’s health during adulthood. This article reviews the current evidence regarding maternal and early childhood nutritional exposures and their role in epigenetic aging. Recent Findings Maternal and early life consumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…During pregnancy, a multitude of interactions between genetic and environmental factors plays a fundamental role in fetal development [ 1 , 2 ], and, among environmental factors, maternal nutrition plays a critical role in influencing fetal health development as well as the short- and long-term health of the child [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, a multitude of interactions between genetic and environmental factors plays a fundamental role in fetal development [ 1 , 2 ], and, among environmental factors, maternal nutrition plays a critical role in influencing fetal health development as well as the short- and long-term health of the child [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others include histone-modification and expression of noncoding RNAs (miRNA, lncRNA). Epigenetic involvement in the long-term legacy after critical illness appears plausible, as aberrant epigenetic changes have been linked to abnormal development and disease resulting from adverse environmental exposures/stressors [11][12][13][14][15][16].…”
Section: The Epigenetic Legacy Of Critical Illness and Icu Feedingmentioning
confidence: 99%
“…Aberrant epigenetic changes have been linked to abnormal development and long-term disease resulting from adverse environmental exposures, such as early-life or other stress and inadequate nutrition [11][12][13][14][15][16]. Critical illness imposes extreme stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [ 75 ] have demonstrated the link between the genome and environment in the development of osteoporosis and vitamin D, and its receptor VDR may act as a mediator. Other studies, both in animal models and in humans, found an association between vitamin D deficiency during pregnancy and the risk of medical conditions in offspring, such as inflammation and adiposity [ 76 ], allergies [ 77 ], ageing [ 78 ], and osteoporosis [ 79 ] via epigenetic modifications. In a review by Snegarova et al, hypovitaminosis D was associated with an increased incidence of obesity, insulin resistance, diabetes, and osteoporosis, all conditions that are associated with nephrolithiasis [ 80 ].…”
Section: Food Compoundsmentioning
confidence: 99%